RANCANG BANGUN SISTEM PEMANEN ENERGI EXHAUST FAN DENGAN DIFFUSER TURBIN ANGIN SUMBU HORIZONTAL - Edyama Vasabri Genta Maulana; I Wayan Sukerayasa; Cok Gede Indra Partha (Jurnal SPEKTRUM, 2021)
Utilization of waste energy from exhaust fan air needs to be optimized considering thereis great potential where exhaust fan is widely used in the industrial sector. Exhaust wind fromexhaust fan can be utilized to generate electricity with horizontal wind turbine. Thecharacteristics of exhaust energy from exhaust fan that spreads and has medium to low speed,therefore its requires an optimization to get maximum wind energy from exhaust fan, one ofthem by the addition of a diffuser that can increase the performance of wind turbines byfocusing the wind around the rotor. Designing diffuser conducted using AutoDesk Inventor andsimulation CFD (Computational Fluid Dynamic) with SolidWorks. The results of this studyindicate, horizontal wind turbine with diffuser can increase wind turbine power up to 47.61% andincrease turbine rotational speed (rpm) up to 23.48% compared to wind turbines without adiffuser.